Comprehension, Sense and Pedagogy - Cárdenas Páez, Alfonso; McNeil Fernández, Alejandro; Malaver Rodríguez, Rodrigo (Colombian Applied Linguistics Journal, 2012)
This text, based on Bakhtin’s perspective, sees language as a condition for the construction of reality. The subject’s understanding of reality is always determined by situational circumstances (event) and the way individuals experience and perceive these events. The various senses are the result of different positions from which the other speakers participate (create). The perceptions of the subject are not passive, they are charged with willingness to play with intertexts, interdiscourses and antidiscourses that foster dialogue, and this, in turn, is evidence of and possibility of understanding. All this is important in the pedagogical arena, and this is why the text closes by opening a deeper discussion in this regard.